DEVELOPMENT OF CERVICAL INTRAEPITHELIAL NEOPLASIA AND INVASIVE CERVICAL CANCER DUE TO OXIDATIVE STRESS - Asotić, Amir; Asotić Memić , Anida; Memić, Muhamed; Asotić, Kerim; Asotić, Amra (Sanamed, 2024)
Background: Cervical cancer (CC) ranks third among all malignant diseases of the female reproductive system. CC arises through a series of pathological changes called cervical intraepithelial neoplasia (CIN). Timely diagnosis and treatment of CIN are essential in the prevention of CC. Oxidative stress (OS) presents a major risk factor in the pathogenesis of both CC and CIN. This study aimed to determine the association between OS and the pathohistological severity of cervical lesions.Materials and Methods: The research was conducted at the Clinical Center of the University of Sarajevo on 240 female respondents divided into two groups. The experimental group consisted of 200 women with changes consistent with CIN, carcinoma in situ (CIS), and CC determined by biopsy, divided into 5 subgroups (CIN 1, CIN 2, CIN 3, CIS, and CC) with 40 respondents per group. The control group (N=40) had biopsy findings that were non-pathological. The concentration of acid thiobarbituric reactive substances (TBARS) was determined for all subjects from bioptic samples using the spectrophotometric method and according to standard laboratory practice.Results: Our results showed a significant difference in age between patients with CIN 1, CIN 2, and CIN 3 and the control group as well as when compared to patients with CC. The oldest group comprised patients with CC. Tissue TBARS levels in the CIS group were significantly higher than that of the control group (p
Keywords: oxidative stress; cervical intraepithelial neoplasia; cervical cancer